3x-3=2x-12

Simple and best practice solution for 3x-3=2x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-3=2x-12 equation:


Simplifying
3x + -3 = 2x + -12

Reorder the terms:
-3 + 3x = 2x + -12

Reorder the terms:
-3 + 3x = -12 + 2x

Solving
-3 + 3x = -12 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-3 + 3x + -2x = -12 + 2x + -2x

Combine like terms: 3x + -2x = 1x
-3 + 1x = -12 + 2x + -2x

Combine like terms: 2x + -2x = 0
-3 + 1x = -12 + 0
-3 + 1x = -12

Add '3' to each side of the equation.
-3 + 3 + 1x = -12 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = -12 + 3
1x = -12 + 3

Combine like terms: -12 + 3 = -9
1x = -9

Divide each side by '1'.
x = -9

Simplifying
x = -9

See similar equations:

| 5v^2+6v+7=v^2-4v | | 3d-12=-3 | | 0.4w-11=-0.5w | | 6+n=28+9 | | 2x+27=5x-3 | | r=50x-200 | | 188=-2x+4(6x-8) | | -8-3n=1 | | a+6=98 | | 3x+8=7x-12 | | 3x-2=2x-2 | | 98=7x+3(4x-18) | | 4c-6=3 | | x^2+20x= | | 0=.75x+75 | | -10x-10=-6x-30 | | 13x-4=6x+24 | | -y-15+9y=3y+2+4y | | 3w-18w=-60 | | 14=-(-6-8) | | 3x-r(x-1)=2(7-3x) | | 6(7n-4)-1=12+5n | | y=0.12x+17.52 | | 5x+72367=109917 | | 2x+1=2y+5 | | 1.25+a=2a+1 | | 7+2x=30 | | 2+y/6=-13 | | (x+2)(5x-4)=0 | | 2x^2=3+9x | | 7x-6=3x+14 | | 10e+2e-9=39 |

Equations solver categories